Accounting Method for Carbon Emission Obligation on Load Side of Power System Based on Peak Load Characteristics - HUANG Yanlu, HU Xudong, LIN Zhenfu, MA Xiyuan (Dianli jianshe)
To accurately estimate the carbon emission obligation of the user side of a new power system and promote the continuous development of low-carbon electricity， this study uses the node carbon intensity calculation method to characterize the carbon flow distribution of the system and preliminarily calculates the carbon emission obligation on the load side. Moreover， under the premise that the total carbon emission obligation allocation amount remains unchanged before and after correction， the initial carbon emission obligation on the load side is modified and analyzed based on an innovative combination of the comprehensive load method， where the peak load characteristics of the user at the current stage are fully considered. Next， considering the long-term changes in electricity demand and emission reduction capabilities on the load side， a carbon emission obligation allocation interval reflecting the long-term electricity consumption characteristics of the users was constructed. Based on this， the satisfaction of each load node with the carbon emission obligation accounting results was accurately evaluated， providing a direction for the formulation of low-carbon transformation strategies and the construction of demand-side response capabilities in the power system. The application results in the 14-node power system show that compared to the initial accounting results of the node carbon intensity allocation method， the load-side carbon emission obligation accounting results based on the user electricity consumption characteristics of the power system are both reasonable and accurate， providing data support for the clean and low-carbon development of the power industry， and have a certain reference value.